Analisis Pendataan Berita Acara Temuan Selisih Berbasis Web pada PT Bank negara Indonesia, Tbk - Yohanes Bowo Widodo; Kiki Kurniawan; Reni Febrianti (Pusat Riset dan Inovasi Nasional, 2021)
Bank Negara Indonesia is a state-owned company that operates as a financial institution that has been around for more than 70 years. However, in its development it turns out that Information Technology has not been applied by all parts of PT. Bank Negara Indonesia, Tbk. In processing the data on the minutes of discrepancy findings. PT. Bank Negara Indonesia, Tbk still uses manual bookkeeping to collect data on findings of discrepancies. So that there are often invalidities and discrepancies in the data collection of the minutes of discrepancies found. Therefore, it is very necessary to have a data collection system for the minutes of discrepancies found. Based on this, it is necessary to create an application system related to data collection of minutes of discrepancies found at PT. Bank Negara Indonesia, Tbk The method that will be used in making the application is using the SSAD method with the steps of Feasibility, Investigation of the Current Environment, Business System Options, Definition Requirements, Technical System Options, Logical Design and Physical Design. With this method, it is hoped that application programs can be created according to the company's needs. With the application of data collection on the minutes of discrepancies found at PT. Bank Negara Indonesia Tbk, the process of finding the difference becomes easier and the data stored is well maintained and can be easily searched.